The Expanding Moral Circle as a Framework Towards Food Sustainability. (1st August 2022) - Herdoiza, Natalie; Worrell, Ernst; Van Den Berg, Floris
Abstract : A shift towards more environmentally friendly and socially responsible food systems is a key step in the achievement of global sustainable development goals. To obtain significant results, however, it is essential to find participative ways to frame food sustainability objectives, so they can speak to a wide array of actors of change. This article addresses the promising potential of empowering actors across the food system to make a shift in their food choices, by facilitating the association of food sustainability values with contemporary moral issues. In this context, a conceptual framework for a transition towards food sustainability is proposed, based upon the concept of the moral circle. This approach transcends the human-centred methods enacted in traditional sustainable development agendas, offering an alternative with a more holistic perspective. It is expected that emphasising moral reflection around sustainability might encourage societal participation in the creation of sustainable, fair and healthier food systems.